Research on the coordinated measurement and spatiotemporal evolution of digital economy empowering ecotourism - Yuan Wang; Yuxin Li; Linling Zheng; Yihua Zhang (PLoS ONE, 2025)
Although the internet economy in China has had enormous growth in recent years, the country’s ecotourism business has shown a far slower rate of expansion. There is an immediate need to discuss how to leverage the digital economy to advance ecotourism and achieve synchronized development between the two. The coupling and coordination between China’s digital economy and ecotourism are examined in this study using a coupling coordination model to evaluate their temporal and geographical growth. Panel data that was gathered from 30 provinces between 2011 and 2022 served as the basis for the research. The historical and geographical evolution of their attributes is examined by the application of standard deviational ellipse analysis, kernel density estimation, and Dagum Gini coefficient. The results show a steady improvement in the degree of connectivity and synchronization between the digital economy and ecotourism. This improvement follows a general geographical trend of being robust in the eastern regions and feeble in the western regions, while being prominent in the southern areas and less significant in the northern areas. The primary cause of the unequal growth of the digital economy and ecotourism in various places is regional inequities, as evidenced by the variable drop in the Gini coefficient of coupling coordination degree. A distinct polarization tendency in the national, eastern, and western areas, along with an annual expansion of the right tail in the national kernel density, cause the kernel density curve to continuously move to the right. The standard deviational ellipse shows that the geographical inequalities between ecotourism and the digital economy are gradually diminishing. The three primary regions are seeing a dynamic reduction in the size of the ellipse, and the distribution of places is becoming more focused. The article suggests enhancing digital transformation in ecotourism and promoting industry growth for better-coordinated development.